Excavation of the Suspect's Identity by Analysis of the Speaker Profiling Case Evidence of Fake Voice Recordings - Tsurayya Yusra Zahirah Zahra; Zhang Wei (Universitas Ahmad Dahlan, 2023)
Technological developments, especially in AI applications, allow someone to commit criminal acts by changing other people's voices. This study implements forensic linguistics by comparing data sources on the audio of Lesti (L) and Rizky Billar (RB) to ensure the originality of the sounds. The Speaker Profiling method with aural-perception analysis is used because there is no valid comparative evidence, so the audio comparison is taken from the L and RB platforms published to the public. This research resulted in two different aspects of each audio: phonetics and acoustics. These two aspects show the two audio sources' differences in pronunciation, emphasis, frequency, and tone. As a result, the vote is identified as a hoax. This research can demonstrate the use of software to help identify individual language profiles; it contributes to the development of applied linguistics, especially as a legal aid tool. Researchers hope that there will be further research from other linguists that will address more benefits of using AI / Corpus technology as a linguistic analysis tool, both with spoken and written data.